2005
DOI: 10.1111/j.1365-2265.2005.02390.x
|View full text |Cite
|
Sign up to set email alerts
|

Serum osteoprotegerin levels are associated with inflammation and pulse wave velocity

Abstract: In summary, serum OPG and baPWV levels are elevated in diabetic patients and serum OPG levels are significantly associated with inflammation and arterial stiffness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
45
2
3

Year Published

2006
2006
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 33 publications
11
45
2
3
Order By: Relevance
“…OPG levels increase with age (14,20), diabetes (12,21), and renal failure (22) and are positively correlated with CRP, interleukin-6, fibrinogen, glycemic status, and insulin resistance (17,23,24). In our study, fasting glucose, creatinine, hsCRP, fibrinogen, and HOMA-IR showed significantly positive correlations with OPG.…”
Section: Discussionsupporting
confidence: 53%
“…OPG levels increase with age (14,20), diabetes (12,21), and renal failure (22) and are positively correlated with CRP, interleukin-6, fibrinogen, glycemic status, and insulin resistance (17,23,24). In our study, fasting glucose, creatinine, hsCRP, fibrinogen, and HOMA-IR showed significantly positive correlations with OPG.…”
Section: Discussionsupporting
confidence: 53%
“…Besides, in our study, testosterone levels were not retained as a predictive variable in the multivariate analysis. Finally, insulin resistance, another common characteristic of PCOS patients, has been shown to correlate either directly (51) or inversely (20) with serum OPG concentrations, but we did not find any statistically significant relationship between serum OPG levels and the insulin sensitivity index.…”
Section: Discussioncontrasting
confidence: 45%
“…The reason for this association is unclear. Two previous reports (in obese subjects (22) and in elderly men (21)) showed a positive relationship between OPG and insulin sensitivity, while a third one in women found no relationship (20); finally, in a fourth study (30), OPG was positively correlated with HOMA index in normal and diabetic subjects. Results of the present study are in line with this last study and show an independent relationship between HOMA index and OPG.…”
Section: Discussionmentioning
confidence: 91%
“…CRP is an acute-phase protein produced predominantly by hepatocytes under the influence of cytokines. The relationship between CRP and OPG was recently studied in subjects with CAD (18), diabetes (30), and long-lived subjects (32) but has never been looked at in obese subjects. On the other hand, despite the positive relationship that we found in our obese group between OPG and SGPT, SGPT was not found to be an independent predictor of OPG suggesting that, at least in healthy obese subjects, there is no direct relationship between OPG and liver function.…”
Section: Discussionmentioning
confidence: 99%